PERAN INTERNAL AUDIT DAN KOMITE AUDIT DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE - Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2010)
Abstract Good Corporate Governance (GCG) is the situation toward good manage in the business, there are transparency and accountability. Therefor, need cooperation of all section within the company , for example top manager until low manager. Exception corporation, the organization need internal control, usually name Internal Control Systems (ICS). Internal Control Systems have been done auditor intern, internal auditors accountable for their duties to the management company. Some companies have the commissioners and shareholder need to audit committe.. In daily activities between internal audit and audit committes should work together in realizing the condition Good Corporate Governance (GCG). Auditor intern have duty to success intern control, and audit committe have duty to review the task of auditor intern and accountability to precident director and shareholder. The members of the committe audit have background at least master degree of accountant and skill as an auditor in the Accoutant Public Corporation. Keywords: Good Corporate Governance, Auditor Intern, Audit Committee and Internal Control Systems (ICS)